Microcomputers in the Schools Implementation in Special Education. Case Study Report. - SRA Technologies, Inc., Arlington, VA.; SRA Technologies, Inc., Arlington, VA.; COSMOS Corp., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The report presents case studies of microcomputer use in 12 school districts' special education programs. The case study approach was designed to focus on organizational issues, specifically the following four: nature of collaboration between regular and special education, centralization or decentralization of decisionmaking in implementation phases, cooperation between administrators and educators regarding application (administrative vs. instructional), and training in the use of microcomputers. An initial section analyzes data across the case studies. Major findings include overall collaboration in the use of microcomputers between special and regular education, especially, at the building rather than district level; the importance of a small team approach to implementation; lack of conflict between administrative and instructional applications in microcomputer systems; and emerging trends in designation of a coordinator to supervise implementation. Each of the 12 case studies reports on program development and chronology, features of the microcomputer system, and organizational aspects. (CL)
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC. Div. of Educational Services.
Contract Number: 300-82-0250.
ERIC Note: For related document, see EC 161 137.
Educational level discussed: Elementary Secondary Education.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Administrator Role; Case Studies; Computer Assisted Instruction; Computer Managed Instruction; Disabilities; Elementary Secondary Education; Microcomputers; Program Development; Program Implementation; School Districts; Teacher Education; Reports, Descriptive; Reports, Evaluative